(untitled) (Bangladesh Journal of Agricultural Research, 2016)
The field experiment was conducted at the Hill Agricultural Research Station, BARI, Khagrachari for the two consecutive years (2009-10 and 2010-11) to find out the wheat variety suitable for hilly environment and investigate the interaction of sowing dates and varieties to recommend the promising variety with proper sowing time. The experiment was laid out in split-plot design with three replications where three dates of sowing (Nov. 20, Nov. 30 and Dec. 10) were assigned in the main plots and five modern wheat varieties (Shatabdi, Sufi, Sourav, Bijoy and Prodip) were tested in the sub-plots. The yield responses of wheat varieties during the two years showed that there were significant varietal differences under the experimental soil and environmental conditions. The variety Bijoy gave maximum grain yield closely followed by Sourav in both years. Shatabdi produced higher yield under early sowing (Nov. 20) but yield was decreased due to late sowing (Dec. 10). Initially the plant population and finally spikes/m2 were affected by late sowing that caused less yield in Shatabdi. The mean yield of all varieties pulled over the sowing time indicated that wheat yield was not affected due to delay sowing up to 10th December. The experimental result demonstrated that Shatabdi could be recommended only for early sowing whereas Bijoy and Sourav could be recommended both for early and late sowing under the experimental soil and environmental conditions at hilly region of Khagrachari. Bangladesh J. Agril. Res. 40(4): 521-528, December 2015